Identification of Neoceratitis asiatica (Becker) (Diptera: Tephritidae) based on morphological characteristics and DNA barcode - Guo, Shaokun; He, Jia; Zhao, Zihua; Liu, Lijun; Gao, Liyuan; Wei, Shuhua; Guo, Xiaoyu; Zhang, Rong; Li, Zhihong (Zootaxa, 2017)
Neoceratitis asiatica (Becker), which especially infests wolfberry (Lycium barbarum L.), could cause serious economic losses every year in China, especially to organic wolfberry production. In some important wolfberry plantings, it is difficult and time-consuming to rear the larvae or pupae to adults for morphological identification. Molecular identification based on DNA barcode is a solution to the problem. In this study, 15 samples were collected from Ningxia, China. Among them, five adults were identified according to their morphological characteristics. The utility of mitochondrial DNA (mtDNA) cytochrome c oxidase I (COI) gene sequence as DNA barcode in distinguishing N. asiatica was evaluated by analysing Kimura 2-parameter distances and phylogenetic trees. There were significant differences between intra-specific and inter-specific genetic distances according to the barcoding gap analysis. The uncertain larval and pupal samples were within the same cluster as N. asiatica adults and formed sister cluster to N. cyanescens. A combination of morphological and molecular methods enabled accurate identification of N. asiatica. This is the first study using DNA barcode to identify N. asiatica and the obtained DNA sequences will be added to the DNA barcode database.